Self-reported diet management, dietary quality, and blood pressure control in Korean adults with hypertension - Jee-Seon Shim; Sun Jae Jung; Hyeon Chang Kim (BMC, 2019)
Abstract Objectives Hypertension control is a major public health concern. Daily preventive practices of the affected individual are essential for controlling blood pressure (BP). We investigated the association of diet management practice, dietary quality, and BP control among Korean adults with known hypertension. Methods We included 4107 participants aged 40-79 years who reported physician-diagnosed hypertension in the Korea National Health and Nutrition Examination Survey 2013-2016. Dietary management practice was defined by self-report, and dietary intakes were assessed by a 24-h dietary recall. Dietary quality and adherence were evaluated based on the Korean Healthy Eating Index (KHEI) using food and nutrient intakes assessed by a 24-h dietary recall. BP control was defined as systolic/diastolic BP < 140/90 mmHg. Results While the prevalence of dietary management was higher in women than men, BP control rate was not different by sex. Dietary management practice had no significant association with BP control in both men and women. Only in men, dietary quality was positively associated with BP control (OR: 1.10 per KHEI 10 score increase, 95% CI: 1.00-1.20, p-value = 0.04). Men who had a highly adherent diet seemed to have a higher possibility of BP control, but there was no statistical significance (OR: 1.54, 95% CI: 0.84-2.81, p-value = 0.16). Conclusions A high-quality diet was positively associated with BP control in Korean men aware of their hypertension. Our findings highlight the beneficial impact of dietary management as a means for achieving blood pressure control.